Application of Cottagecore Visual Development Motifs on Modest Fashion Product - Febriani, Rima; Austriani, Eline (Serat Rupa: Journal of Design, 2025)
The cottagecore trend has been growing and increasing since 2020, this has made many brands adopt cottagecore as their brand concept, and indicates that there is interest from the market to develop cottagecore style clothing in Indonesia, for example, as the Himeka Vintage brand with fairy style clothes such as flowy dresses with floral motifs, Hankaaa.id with dreamy and magical clothes such as fluffy dresses full of lace and ruffles, then the Sausan Official brand with its vintage and elegant clothing characterized by signature patterns and textures. This study aims to explore the potential and develop cottagecore visual elements in modest fashion wear through a design thinking approach, observation data collection, and literature review. The design of motif elements for visual development in fashion products combining several visual representations typical of cottagecore icons, such as mushrooms, homemade bread, strawberry motifs, and butterflies. The motif composition development technique uses the spot repeat grids concept, while in the process of designing fashion products using design theory with the SCAMPER method approach. The outcome of this study is to offer innovation, particularly in motif visuals for clothing that adapts the cottagecore style in the Indonesian fashion industry.